Pelatihan Pengolahan Minyak Goreng Bekas Industri Kerupuk Kulit Menjadi Sabun Padat di Kelurahan Kamang Magek - Ulia, Hasnah; Rahayu, Puji; Rahmad, Dedy; Rosalina, Rosalina; Putri, Dwi Kemala; Nurrahmi, Rara (Politeknik ATI Padang, 2022)
Most of the residents of Kamang Magek work as entrepreneurs. The type of business that is developing a lot is the production of skin crackers or known as